Peran Gizi Dalam Perawatan Kulit Yang Optimal - Tatia Sinta Mariani Manalu; Melda Rubiatun Nabila; Novita Dwi Ramadhani; Ufara Maykasyahrani Azzahroh (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2024)
Beauty has become a social goal that many people dream of, with a perfect body, face and skin considered the key to self-confidence and social status. However, beauty procedures that are often performed in an unhealthy manner, especially extreme diets or neglecting proper nutrition, can lead to skin problems and premature aging. The purpose of this study is to determine the effect of nutrition on skin health, focusing on the role of nutrition in maintaining beauty and preventing premature aging. The research method used was descriptive qualitative research where information was collected through observation and interviews with nutritionist. The results showed that a healthy and balanced diet rich in antioxidants, vitamins and minerals is essential for maintaining healthy skin. Certain nutrients, such as vitamins A, C, E, omega-3 fatty acids and protein, play a special role in skin care. On the other hand, an unhealthy diet, especially fast food that is high in fat and sugar, can lead to skin problems such as acne and premature aging. Therefore, it is important for us to pay attention to our diet and choose the right foods to maintain healthy and beautiful skin.